DAMPAK KREDIT RENTENIR TERHADAP KEUNTUNGAN USAHA PAGANDENG SAYUR DI KECAMATAN PALLANGGA KABUPATEN GOWA - Rusydi, Muhammad; Rasulong, Ismail (Jurnal Ekonomi Balance, 2009)
Abstract This study aimed to test the hypothesis of the variables that influence the variable vegetable pagandeng loan. Knowing how much influence Kentungan Net per month (in%) against the loan pagandeng vegetables. know how much influence Lending per month (in%) against the loan pagandeng vegetables. Determination of the samples was done by purposive random sampling method. The number of samples in this study were 50 respondents Pagandeng Vegetable contained in two main bases points Panciro Bases and Base Cambaya. In quantitatively prove the relationship variables, researchers use econometric approach in the form of regression analysis and correlation. Conclusion of the study is a variable rate of profit is very influential in determining the amount of the loan. The variable interest rate in this study is less a role in determining the loan amount because although the interest rate per month is relatively high, the vegetable pagandeng keep borrowing from moneylenders. Keywords: Credit Rengtenir, Gain Enterprises, Pagandeng Vegetables Penelitian bertujuan menguji hipotesis dari variabel-variabel yang mempengaruhi variabel pinjaman pagandeng sayur. Mengetahui seberapa besar pengaruh Kentungan Bersih per bulan (dalam %) terhadap pinjaman pagandeng sayur. mengetahui seberapa besar pengaruh Bunga Pinjaman per bulan (dalam %) terhadap pinjaman pagandeng sayur. Penentuan sampel dilakukan dengan metode Purposive Random Sampling. Jumlah sampel dalam penelitian ini sebanyak 50 responden Pagandeng Sayur yang terdapat di dua titik pangkalan utama yaitu Pangkalan Panciro dan Pangkalan Cambaya. Dalam membuktikan hubungan variabel secara kuantitatif, peneliti menggunakan pendekatan ekonometrik yang berupa Analisa Regresi dan Korelasi. Kesimpulan hasil penelitian adalah variabel tingkat keuntungan sangat berpengaruh dalam menentukan besarnya jumlah pinjaman. Adapun variabel tingkat bunga dalam penelitian ini kurang berperan dalam menentukan besarnya jumlah pinjaman karena meskipun tingkat bunga pinjaman per bulan relatif tinggi, para pagandeng sayur tetap melakukan pinjaman kepada rentenir. Kata Kunci : Kredit Rengtenir, Keuntungan Usaha, Pagandeng Sayur